ANALISIS HUBUNGAN JANGKA PANJANG DAN JANGKA PENDEK ANTARA NPL, ROE, SIZE DAN LOTA TERHADAP CAPITAL BUFFER - Juni Purwanti; Suwaryo Suwaryo; Sudarto Sudarto (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2016)
This study aimed to analyze the effect of Non-Performing Loans, Return on Equity, bank size, and Loan to Total Assets of the capital buffer using panel data. The population in this study was State Owned Banks registered in Bank Indonesia for the period 2002 to 2014. In this study all the population used as an object of study and the type of data used in this research was quarterly data. Data were analyzed using cointegration test and Error Correction Model to demonstrate short and long term relationship. The results showed that in the short term, the Non Performing Loan and Return on Equity have a positive influence on equilibrium of capital buffers in goverment bank. Furthermore, the size of bank negatively affect the equilibrium of capital buffers in the short term. Besides the long-term relationship, the Non Performing Loan and Return on Equity also has a positive effect on the equilibrium of capital buffers in state-owned commercial banks. Meanwhile, Loan to Total Assets have a negative effect on the equilibrium of capital buffers in the long term.